Comparaison entre moyennes temporelles et microcanoniques : Une contribution à l'étude de l'ergodicité - Benelmostafa, M'hamed (Académie de Bordeaux, Université De Pau et Des Pays De L’Adour, Institut Universitaire de Recherche Scientifique, Pau, 1985)
The present work is concerned with the exact calculation of several microcanonical and time mean over the H = E manifold for a two degree of freedom conservative anc non integrable hamiltonian system. As expected the chaotic behavior is growing with the energy i.e. the difference between time mean f and microcanonical mean is going to zero at high energy. The domain of chaotic behavior is quite the same as found with the Poincaré's map method.
Keywords: Moyenne temporelle; Microcanonique; Ergodicité